2018
DOI: 10.4038/sljch.v47i3.8539
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoea in north Karnataka: Rotavirus versus non-rotavirus

Abstract: Background: As children with diarrhoea are often prescribed antibiotics, it was decided to study the causative organisms. Rotavirus is a major cause of diarrhoea and diarrhoea related mortality in most parts of India. Rotavirus vaccine is available but expensive. According to the World Health Organisation (WHO) the vaccine should be used in areas where diarrhoea related under five mortality is around 10%. The situation in north Karnataka is not known. Objectives: To find proportions of rotavirus and nonrotavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…12 With ELISA, we observed a 30.19% prevalence of rotavirus-induced diarrhea in children under the age of five. The findings of this study were corroborated by reports from different parts of India, including Mumbai, Maharashtra 28%, 13 Vijayapur, Karnataka 31%, 14 Agartala, Tripura 36% . 15 In our study, the highest prevalence of rotavirus infection was observed in male children (52.6%) compared to female children (47.4%), with a male-to-female ratio of 1.1:1.…”
Section: Discussionsupporting
confidence: 89%
“…12 With ELISA, we observed a 30.19% prevalence of rotavirus-induced diarrhea in children under the age of five. The findings of this study were corroborated by reports from different parts of India, including Mumbai, Maharashtra 28%, 13 Vijayapur, Karnataka 31%, 14 Agartala, Tripura 36% . 15 In our study, the highest prevalence of rotavirus infection was observed in male children (52.6%) compared to female children (47.4%), with a male-to-female ratio of 1.1:1.…”
Section: Discussionsupporting
confidence: 89%